Enhancing University Students’ Reading Comprehension through Local Wisdom-Based Materials and Problem-Based Learning - Lanlan Muhria; Sri Wuli Fitriati; Suwandi Suwandi; Sri Wahyuni (Jurnal Pemberdayaan Masyarakat, 2026)
This research investigates the?integration of local wisdom-based reading materials into an effective problem-based learning model in enhancing university students’ reading comprehension. The study was inspired by the lack of cultural relevance of reading material often sourced from other countries and not aligned with ?students' backgrounds. A pre-experimental mixed-methods design was used with 33 students, who received the reading comprehension pre- and post-tests and an interview. Quantitative data were analyzed using paired-samples t-tests and N-Gain, while qualitative data were analyzed descriptively. The results showed an improvement in the post-test scores of students who used local wisdom-based materials, with a very high N-Gain, indicating that LKBKpBL based on PBL can be categorized as effective. Additional outcomes indicated improvements in motivation,?critical and reflective thinking, collaboration, and cultural identity. The research recommends that fostering local wisdom in PBL is not only helpful for enhancing understanding and perception but also for maintaining cultural insight and interaction. Educationally, the findings contribute to literacy education by presenting a culturally responsive, problem-based instructional framework that fosters students’ ability to relate reading to their cultural experiences, sustain higher learning outcomes, and maintain local value relevance in institutions of higher learning.